PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 51 PEKANBARU - Kusmiati Kusmiati; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted aims to overcoming the difficulties students at once petrified in first grade students of SDN 51 Pekanbaru in the addition and subtraction of two-digit numbers. In particular the objectives of this research is to improve student learning outcomes of Mathematics class I SDN 51 Pekanbaru using Indonesian Realistic Mathematics Education (IRME). The low yield was due to the students' learning during the teacher in providing rare examples using concrete objects related to the everyday world of students so that students are less motivated to learn. This research was conducted at SDN 51 Pekanbaru in the second semester of the academic year 2014 / 2015. This classroom action research will be carried out at SDN 51 Pekanbaru. As the subject of this research is the first grade students of SDN 51 Pekanbaru the number of students 37 consisting of 17 men and 20 women. The result of research using PMRI can improve student in the learning process. In addition, the activities of teachers also increased, according to the lesson plans were designed. So that the student learning experience increased. In first cycle obtained 38.98% increase in learning outcomes and classically completeness obtained at 97.30% and the second cycle was also obtained increase of 42.71% and classically completeness obtained at 97.30 %. The conclusion of this research is the application of Indonesian Realistic Mathematics Education approach (IRME) can increase student learning outcomes of mathematics class I SDN 51 Pekanbaru.Keywords: Indonesian Realistic Mathematics Education (IRME), Mathematics Learning Outcomes